2020
DOI: 10.1186/s13046-020-01582-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapeutic strategies targeting telomere maintenance mechanisms in high-risk neuroblastoma

Abstract: The majority of high-risk neuroblastomas can be divided into three distinct molecular subgroups defined by the presence of MYCN amplification, upstream TERT rearrangements or alternative lengthening of telomeres (ALT). The common defining feature of all three subgroups is altered telomere maintenance; MYCN amplification and upstream TERT rearrangements drive high levels of telomerase expression whereas ALT is a telomerase independent telomere maintenance mechanism. As all three telomere maintenance mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 100 publications
2
37
0
Order By: Relevance
“…George et al [101] recently evaluated the clinical ATR inhibitor AZD6738 in a panel of telomerase-and ALT-positive NB and non-NB cell lines, and found that ALT-positive cells were generally not more sensitive to ATR inhibition than telomerase-positive cells are following ATR inhibition. These findings provide support for differences in ATR inhibitor sensitivity not being related to ATRX-deficient ALT [100].…”
Section: Therapies Against Altmentioning
confidence: 99%
“…George et al [101] recently evaluated the clinical ATR inhibitor AZD6738 in a panel of telomerase-and ALT-positive NB and non-NB cell lines, and found that ALT-positive cells were generally not more sensitive to ATR inhibition than telomerase-positive cells are following ATR inhibition. These findings provide support for differences in ATR inhibitor sensitivity not being related to ATRX-deficient ALT [100].…”
Section: Therapies Against Altmentioning
confidence: 99%
“…This review provides an overview of the current state‐of‐the‐art molecular understanding of the development and progression of NB, with a particular emphasis on genetic aberrations and disrupted molecular pathways. As noted, several excellent reviews have been published, covering recent advances made in pathogenesis, diagnosis, and clinical management of NB and interested readers are referred to those excellent publications 4,9,22,29,42,46–72 . In this review, we will emphasize how these advances in knowledge about molecular pathogenesis can be translated to developing molecular targeted therapies for NB management, especially personalized therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Further probes were selected to detect ALK mutations or amplifications [19,20,45], focusing on the most common druggable mutations present in neuroblastoma, and genes involved in the p53/MDM2-and Ras/MAPK-pathway, as mutations of these genes have been previously shown to define a group of UHR neuroblastomas [13]. Finally, we included probes covering additional genes previously found mutated in neuroblastoma [9][10][11][12][13]18,46], and with potential relevance for neuroblastoma tumor biology or targeted therapies, including ATM [47] and ATR [48,49] (Table S1). The NB-HCPS assay includes 4516 single probes that cover 2484 genomic regions, including 55 genes (Figure 1A, Tables S1 and S2), 736694 base pairs (bp) in total, as well as 65 additional probes across the genome serving as a reference for copy number analysis.…”
Section: Design Of a Neuroblastoma Panel Sequencing Assaymentioning
confidence: 99%